2016
DOI: 10.1261/rna.056259.116
|View full text |Cite
|
Sign up to set email alerts
|

Evolving specificity of tRNA 3-methyl-cytidine-32 (m3C32) modification: a subset of tRNAsSer requires N6-isopentenylation of A37

Abstract: Post-transcriptional modifications of anticodon loop (ACL) nucleotides impact tRNA structure, affinity for the ribosome, and decoding activity, and these activities can be fine-tuned by interactions between nucleobases on either side of the anticodon. A recently discovered ACL modification circuit involving positions 32, 34, and 37 is disrupted by a human disease-associated mutation to the gene encoding a tRNA modification enzyme. We used tRNA-HydroSeq (-HySeq) to examine 3 methyl-cytidine-32 (m 3 C32), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(122 citation statements)
references
References 56 publications
(72 reference statements)
5
113
0
Order By: Relevance
“…This suggested that the t 6 A 37 found on the tRNAs Thr and tRNA Ser GCU, might be required for m 3 C 32 formation [133]. Dependency of m 3 C 32 on t 6 A 37 was indeed reported for tRNAs Thr in S. cerevisiae [148] (also see below).…”
Section: Interdependence Of Position 37 Modifications In Eukaryalmentioning
confidence: 84%
See 4 more Smart Citations
“…This suggested that the t 6 A 37 found on the tRNAs Thr and tRNA Ser GCU, might be required for m 3 C 32 formation [133]. Dependency of m 3 C 32 on t 6 A 37 was indeed reported for tRNAs Thr in S. cerevisiae [148] (also see below).…”
Section: Interdependence Of Position 37 Modifications In Eukaryalmentioning
confidence: 84%
“…We highlight two recent cases that involve position 37 of different tRNAs, the yW37 and i 6 A 37 of tRNA Phe and tRNAs Ser , respectively and their interdependent modifications elsewhere in their anticodon stem loop (ASL) [133,134] (Figure 5C). Regarding the position 37 modifications of these tRNAs, while bacterial tRNAs Phe and other bacterial tRNAs that decode UNN codons contain i 6 A 37 , the tRNAs Phe in eukaryotes almost without exception contain the hypermodified G nucleotide, yW37.…”
Section: Interdependence Of Position 37 Modifications In Eukaryalmentioning
confidence: 99%
See 3 more Smart Citations